A Review Study on Biological Therapy and Dentistry (International Journal of Food and Nutritional Sciences, 2022)
Background: The treatment of autoimmune, allergy, infectious, and many other disorders has recently undergone a radical change thanks to a new class of medications. This novel class of medications consists of three groups—cytokines, monoclonal antibodies, and fusion proteins—that may only target particular damaged cells. These medications could cause infections, hypersensitivity, hematologic problems, malignancy, hepatotoxicity, and neurologic issues as side effects. The mechanism of action and adverse effects of these medications, however, are not well understood due to a lack of data or extensive trials. Patients undergoing biological therapy might require particular care in dental procedures. The classification, method of action, side effects, and dental considerations for patients undergoing biological therapy are all reviewed in this essay.